From R&D to productivity through micro level restructuring - Mika Maliranta (The Research Institute of the Finnish Economy (ETLA), 2002)
This paper investigates the determinants of the between component of aggregate productivity growth, which gauges the productivity-enhancing part of plant-level restructuring. Results obtained from a panel of twelve Finnish manufacturing industries in the period from the mid-70s to the late 90s suggest that R&D contributes to aggregate productivity growth through plant-level restructuring with a lag of some 3 to 5 years. More generally, our empirical evidence is in keeping with the conjecture that the technology advances made in the industries, generated or captured by R&D efforts, initially tend to widen productivity dispersion between plants, but the plant-level restructuring needed to fully reap the fruits of technology improvements at the industry level simultaneously compresses the heterogeneity. We observe that international trade, and imports in particular, is positively related to the between component. This finding can be interpreted so that the competitive pressure being one important element of the creative destruction process. Finally, we do not find evidence that wage dispersion between plants stimulates labour reallocation in a productivity- enhancing way. – productivity ; total factor productivity ; plant level restructuring ; R&D ; international trade ; competition – – Tutkimuksessa selvitetään, mitkä tekijät selittävät aggregaattituottavuuden kasvun osuussiirtymäkomponenttia, joka mittaa tuottavuutta vahvistavan osan toimipaikkatason rakennemuutoksesta. Kaksitoista toimialaa 1970-luvun puolivälistä 1990-luvun loppuun käsittävästä paneeliaineistosta saadut tulokset viittaavat siihen, että T&K vaikuttaa aggregaattitason tuottavuuteen toimipaikkatason rakennemuutoksen kautta noin 3-5 vuoden viiveellä. Yleisesti ottaen empiirinen evidenssi on sopusoinnussa sen otaksuman kanssa, että toimipaikkatason rakennemuutosta tarvitaan teknologisten parannusten täysimääräiseen hyödyntämiseen ja että tämä prosessi samaan aikaan tiivistää heterogeenisuutta. Havaitaan, että kansainvälinen kauppa ja tuonti eritoten ovat positiivisessa yhteydessä osuussiirtymäkomponentin kanssa. Tämä havainto on tulkittavissa niin, että kilpailun luoma paine on yksi merkittävä luovan tuhon prosessin elementti. Lopuksi, empiirinen näyttö ei viittaa siihen, että toimipaikkojen väliset palkkaerot vilkastuttaisivat työvoiman uudelleenkohdentumista tuottavuutta vahvistavalla tavalla.
Keywords: O12; O14; O19; O31; O47; 330; Produktivität; Forschung; Verarbeitendes Gewerbe; Finnland